Positive electrode active material for rechargeable lithium battery, method of preparing same, and rechargeable lithium battery including same

By using lithium-nickel transition metal composite oxide as positive electrode active substances and forming an aluminum-containing coating on its surface, the problem that positive electrode active substances in the prior art is difficult to achieve high capacity, high energy density and long life at the same time, and high efficiency and safe lithium battery performance are achieved.

CN119920866APending Publication Date: 2025-05-02SAMSUNG SDI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411544385.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-31
Filing Date
2024-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

It is difficult for the positive electrode active substances of existing rechargeable lithium batteries to achieve high capacity, high energy density and long life at the same time.

Method used

Li-nickel transition metal composite oxide is used as the positive electrode active material, which specifically includes a nickel content of 70 mol % or more, a cobalt content of 0 mol % to 0.01 mol %, and an aluminum-containing coating is formed on the surface, with an aluminum content of between 10 mol % and 35 mol %. The material is determined by EDS measurement based on the total amount of elements containing an aluminum coating.

Benefits of technology

While achieving high capacity and high energy density, the battery life characteristics and safety are improved, and the occurrence of side reactions is suppressed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920866A_ABST
    Figure CN119920866A_ABST
Patent Text Reader

Abstract

Disclosed are a positive electrode active material for a rechargeable lithium battery, a method of preparing the same, and a rechargeable lithium battery including the same. A positive electrode active material for a rechargeable lithium battery includes a lithium nickel-based transition metal composite oxide, in which the lithium nickel-based transition metal composite oxide has a nickel content of 70 mol% or more and a cobalt content of 0 mol% to 0.01 mol% based on a total content of all metals other than lithium in the lithium nickel-based transition metal composite oxide. The lithium nickel-based transition metal composite oxide includes a lithium nickel-based active material and an aluminum-containing coating layer formed on a surface of the lithium nickel-based active material, and the aluminum-containing coating layer has an aluminum content of 10 mol% to 35 mol% as measured by EDS.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2023-0148103 filed on October 31, 2023 in the Korean Intellectual Property Office, the disclosure of which is incorporated herein in its entirety by reference. Technical Field

[0003] The present disclosure relates to a positive electrode active material for a rechargeable lithium battery, a method of preparing the same, and a rechargeable lithium battery including the same. Background Art

[0004] In recent years, with the rapid popularization of electronic devices (e.g., battery-operated electronic devices) using batteries (such as mobile phones, notebook computers, and electric vehicles), the demand for high energy density and high capacity secondary batteries has grown rapidly. Therefore, various research and development efforts have been actively carried out to improve the performance of rechargeable lithium batteries.

[0005] A rechargeable lithium battery includes a positive electrode and a negative electrode each containing an active material that allows lithium ion intercalation and deintercalation (e.g., capable of intercalating and deintercalating lithium ions), and an electrolyte. The rechargeable lithium battery generates electricity through oxidation and reduction reactions during intercalation / deintercalation of lithium ions in the positive electrode and the negative electrode.

[0006] Various positive electrode active materials have been tested to realize (e.g., manufacture) rechargeable lithium batteries. In particular, lithium nickel oxide, lithium nickel manganese cobalt composite oxide, lithium nickel cobalt aluminum composite oxide and lithium cobalt oxide can be used as positive electrode active materials. It is necessary to develop new positive electrode active materials that can achieve high capacity and high energy density while ensuring (e.g., ensuring) long life. Summary of the invention

[0007] Aspects according to one or more embodiments of the present disclosure relate to a positive electrode active material for a rechargeable lithium battery and a method for preparing the same, the positive electrode active material having a cobalt content (e.g., amount) of 0 mol% to 0.01 mol% based on the total content of all metals other than lithium in the positive electrode active material, and can improve life while achieving (e.g., achieving) high capacity.

[0008] An aspect according to one or more embodiments of the present disclosure is directed to a rechargeable lithium battery including a positive electrode active material for a rechargeable lithium battery.

[0009] According to one or more embodiments of the present disclosure, a positive electrode active material for a rechargeable lithium battery includes a lithium nickel transition metal composite oxide, wherein the lithium nickel transition metal composite oxide has a nickel content of 70 mol% or greater and a cobalt content of 0 mol% to 0.01 mol% based on the total content of all metals other than lithium in the lithium nickel transition metal composite oxide, and the lithium nickel transition metal composite oxide includes a lithium nickel active material and an aluminum-containing coating formed on the surface of the lithium nickel active material, and the aluminum-containing coating has an aluminum content of 10 mol% to 35 mol% measured by energy dispersive X-ray spectroscopy (EDS). That is, according to one or more embodiments of the present disclosure, the positive electrode active material for a rechargeable lithium battery includes a lithium nickel transition metal composite oxide, wherein the lithium nickel transition metal composite oxide includes a lithium nickel active material and an aluminum-containing coating formed on the surface of the lithium nickel active material, in which the lithium nickel transition metal composite oxide, the amount of nickel is 70 mol% or greater, and the amount of cobalt is 0 mol% to 0.01 mol%, each amount being based on the total molar amount of all metals except lithium in the lithium nickel transition metal composite oxide, and based on the total amount of all elements in the aluminum-containing coating measured by EDS, the amount of aluminum in the aluminum-containing coating is 10 mol% to 35 mol%.

[0010] According to one or more embodiments of the present disclosure, a method for preparing a positive electrode active material for a rechargeable lithium battery includes: preparing a primary positive electrode active material by wet-coating the surface of a lithium nickel-based active material with an aluminum source in a first solution containing a lithium nickel-based active material having a cobalt content of 0 mol% to 0.01 mol%, an aluminum source, and a solvent; and preparing a final positive electrode active material by heat treatment of the primary positive electrode active material, wherein the content of the aluminum source in the first solution is less than 2 mol% based on the total content of all metals except lithium in the lithium nickel-based active material and the heat treatment is performed at a temperature greater than 700°C to 750°C. That is, according to one or more embodiments of the present disclosure, a method for preparing a positive electrode active material for a rechargeable lithium battery includes: wet-coating the surface of a lithium nickel-based active material having a cobalt content of 0 mol% to 0.01 mol% with an aluminum source in a first solution to prepare a primary positive electrode active material, the first solution comprising a lithium nickel-based active material, an aluminum source and a solvent; and heat-treating the primary positive electrode active material at a temperature greater than 700°C to 750°C to prepare a positive electrode active material, wherein the aluminum of the aluminum source is present in the first solution in an amount less than 2 mol% based on the total molar amount of all metals except lithium in the lithium nickel-based active material.

[0011] According to one or more embodiments of the present disclosure, a rechargeable lithium battery includes: a positive electrode including a positive electrode active material for a rechargeable lithium battery; a negative electrode; and an electrolyte.

[0012] Embodiments of the present disclosure provide a positive electrode active material for a rechargeable lithium battery and a rechargeable lithium battery including the positive electrode active material, which can achieve (e.g., achieve) high capacity and high energy density, and have good life characteristics and safety features while suppressing side reactions that form gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 is a schematic illustration of a cylindrical battery according to some embodiments.

[0014] Figure 2 is a schematic illustration of a prismatic battery according to some embodiments.

[0015] Figure 3 is a schematic illustration of a pouch-type or similar battery according to some embodiments.

[0016] Figure 4 is a schematic illustration of a pouch-type or similar battery according to some embodiments.

[0017] Figure 5 FIG. 5 is a graph depicting the aluminum content based on the total content of nickel, manganese, and aluminum on the uppermost surface of the positive electrode active material measured by EDS in Examples and Comparative Examples.

[0018] Figure 6 4 is a graph depicting formation capacities of rechargeable lithium batteries of Examples and Comparative Examples according to the number of cycles, wherein ■ is Example 1, ● is Example 2, ▲ is Comparative Example 1, and ◆ is Comparative Example 2.

[0019] Figure 7 Graph depicting the capacity of rechargeable lithium batteries prepared in Examples and Comparative Examples according to the number of cycles in a high temperature life evaluation at 45° C., wherein ■ is Example 1, ● is Example 2, ★ is Example 3, ▲ is Comparative Example 1, and ◆ is Comparative Example 2.

[0020] Figure 8 is a graph depicting the outgassing amounts of rechargeable lithium batteries prepared in Examples and Comparative Examples. DETAILED DESCRIPTION OF THE INVENTION

[0022] Hereinafter, exemplary embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. However, it should be understood that the following embodiments are provided in an illustrative manner, and the present disclosure is not limited thereto and is defined only by the claims and their equivalents.

[0023] If (for example, when) any element is referred to as being disposed (or located or placed) "on" (or "below") or "over" (or "under") a component, it may mean that the element is placed in contact with the upper (or lower) surface of the component, and may also mean that another component may be inserted between the component and the element disposed (or located or placed) on (or under) the component.

[0024] Throughout the specification, unless otherwise specified, each element may be singular or plural. In addition, throughout the specification, unless otherwise specified, if (for example, when) "A and / or B" is stated, it means "A", "B", or "A and B".

[0025] As used herein, "combinations thereof" may refer to mixtures, stacks, composites, copolymers, alloys, blends, and / or reaction products of the components.

[0026] Unless otherwise defined herein, the term "particle size" may refer to an average particle size. In addition, the average particle size refers to the average particle size (D 50 ), which is the particle size corresponding to 50% by volume in the volume cumulative distribution of the corresponding particles. The average particle size can be measured by any appropriate method (e.g., in the art), such as by a particle size analyzer, a transmission electron microscope image, or a scanning electron microscope image. In one or more embodiments, the average particle size (D 50 ) can be measured by counting the number of particles in each particle size range using a device using a dynamic light scattering method to analyze the data, and then calculating the average particle size (D) based on the analyzed data. 50 In one or more embodiments, the average particle size (D 50 ) can be measured by laser diffraction. For example, in the measurement by laser diffraction, the target particles are dispersed in a dispersant, introduced into a commercially available laser diffraction particle analyzer (e.g., Microtrac MT 3000), and ultrasonic waves of about 28 kHz are irradiated at a power of 60 W, and then the average particle diameter (D ) corresponding to 50 volume % (vol %) in the cumulative volume distribution of the particles in the measuring device is calculated. 50 ).

[0027] Herein, “energy dispersive spectrum (EDS)” may be a value measured at an acceleration voltage of 2.5 kV to 3.5 kV under the condition that a sample has a reaction depth of 100 μm to 150 μm.

[0028] As used herein to express a specific numerical range, "X to Y" refers to values ​​greater than or equal to X and less than or equal to Y (X≤ and ≤Y).

[0029] Positive electrode active material

[0030] The positive electrode active material includes a lithium nickel transition metal composite oxide. Based on the total content (100 mol%) of all metals in or except lithium in the lithium nickel transition metal composite oxide, the lithium nickel transition metal composite oxide has a cobalt content (e.g., amount) of 0 mol% to 0.01 mol%. That is, based on 100 mol% of all metals (including nickel and any other transition metals) except lithium in the lithium nickel transition metal composite oxide, cobalt is not included or the amount of cobalt included does not exceed 0.01 mol%. Cobalt has an important influence on the life and stability of the positive electrode active material. Although the cobalt content is 0 mol% to 0.01 mol%, the lithium nickel transition metal composite oxide can improve the life and stability of the positive electrode active material. For example, the lithium nickel transition metal composite oxide may have a cobalt content of 0 mol%, 0.001 mol%, 0.002 mol%, 0.003 mol%, 0.004 mol%, 0.005 mol%, 0.006 mol%, 0.007 mol%, 0.008 mol%, 0.009 mol% or 0.01 mol%, for example, the lithium nickel transition metal composite oxide may have a cobalt content of 0 mol%. That is, the lithium nickel transition metal composite oxide may not include cobalt.

[0031] Based on the total content (100 mol%) of all metals other than lithium in the lithium nickel transition metal composite oxide, the lithium nickel transition metal composite oxide has a nickel content (e.g., amount) of 70 mol% or more. Within this range, the positive electrode active material can exhibit improved capacity characteristics. For example, based on the total content of all metals other than lithium in the lithium nickel transition metal composite oxide, the nickel content of the lithium nickel transition metal composite oxide may be 70 mol% to 99 mol%, 70 mol% to 90 mol%, 70 mol% to 85 mol%, or 70 mol% to 80 mol%. For example, the nickel content of the lithium nickel transition metal composite oxide may be 70 mol%, 71 mol%, 72 mol%, 73 mol%, 74 mol%, 75 mol%, 76 mol%, 77 mol%, 78 mol%, 79 mol%, 80 mol%, 81 mol%, 82 mol%, 83 mol%, 84 mol%, 85 mol%, 86 mol%, 87 mol%, 88 mol%, 89 mol%, 90 mol%, 91 mol%, 92 mol%, 93 mol%, 94 mol%, 95 mol%, 96 mol%, 97 mol%, 98 mol% or 99 mol%.

[0032] According to one embodiment, the lithium nickel transition metal composite oxide may be a lithium nickel manganese aluminum transition metal composite oxide, which has a nickel content of 70 mol% or more based on the total content (100 mol%) of nickel, manganese and aluminum in the lithium nickel manganese aluminum transition metal composite oxide. Within this range, the positive electrode active material can exhibit improved capacity characteristics. For example, the nickel content of the lithium nickel manganese aluminum transition metal composite oxide may be 70 mol% to 99 mol%, 70 mol% to 90 mol%, 70 mol% to 85 mol% or 70 mol% to 80 mol%. For example, the nickel content of the lithium nickel manganese aluminum transition metal composite oxide can be 70 mol%, 71 mol%, 72 mol%, 73 mol%, 74 mol%, 75 mol%, 76 mol%, 77 mol%, 78 mol%, 79 mol%, 80 mol%, 81 mol%, 82 mol%, 83 mol%, 84 mol%, 85 mol%, 86 mol%, 87 mol%, 88 mol%, 89 mol%, 90 mol%, 91 mol%, 92 mol%, 93 mol%, 94 mol%, 95 mol%, 96 mol%, 97 mol%, 98 mol% or 99 mol%.

[0033] According to one embodiment, the lithium nickel transition metal composite oxide may be a lithium nickel manganese aluminum transition metal composite oxide, which has a manganese content (e.g., amount) of 10 mol% or more based on the total content (100 mol%) of nickel, manganese and aluminum in the lithium nickel manganese aluminum transition metal composite oxide. Within this range, the positive electrode active material can exhibit improved capacity characteristics. For example, the manganese content of the lithium nickel manganese aluminum transition metal composite oxide may be 10 mol% to 30 mol%, 15 mol% to 30 mol%, or 20 mol% to 30 mol%. For example, the manganese content of the lithium nickel transition metal composite oxide may be 10 mol%, 11 mol%, 12 mol%, 13 mol%, 14 mol%, 15 mol%, 16 mol%, 17 mol%, 18 mol%, 19 mol%, 20 mol%, 21 mol%, 22 mol%, 23 mol%, 24 mol%, 25 mol%, 26 mol%, 27 mol%, 28 mol%, 29 mol% or 30 mol%.

[0034] According to one embodiment, the lithium nickel transition metal composite oxide may be a lithium nickel manganese aluminum transition metal composite oxide, which has an aluminum content (e.g., amount) of less than 4 mol% based on the total content (100 mol%) of nickel, manganese and aluminum in the lithium nickel manganese aluminum transition metal composite oxide. That is, based on the total content (100 mol%) of nickel, manganese and aluminum, the amount of aluminum included may be positive (greater than 0 mol%) and less than 4 mol%. Within this range, the positive electrode active material can easily achieve an improvement in life. For example, the aluminum content of the lithium nickel manganese aluminum transition metal composite oxide may be 1 mol% to less than 4 mol%, 1 mol% to 3 mol%, or 2 mol% to 3 mol%.

[0035] Herein, the "nickel content", "manganese content", "aluminum content" and "cobalt content" of the lithium nickel-based transition metal composite oxide can be measured by an appropriate (e.g., known in the art) method, for example, by an inductively coupled plasma (ICP) method.

[0036] The positive electrode active material (e.g., a lithium nickel-based transition metal composite oxide) includes a lithium nickel-based active material and an aluminum-containing coating formed on the surface of the lithium nickel-based active material, wherein the aluminum-containing coating has an aluminum content (e.g., amount) of 10 mol% to 35 mol% measured by EDS based on the total amount of all elements in the aluminum-containing coating.

[0037] As used herein, "aluminum-containing coating" may refer to the entire region or layer present from the uppermost surface of the positive electrode active material to the uppermost surface of the lithium nickel-based active material. For example, the aluminum-containing coating may refer to a layer present on the outermost surface of the lithium nickel-based active material. The lithium nickel-based active material has a substantially uniform composition that is different from the composition of the aluminum-containing coating, for example, the aluminum content (or amount, for example, in mol% or wt%) in the aluminum-containing coating is greater than the aluminum content in the lithium nickel-based active material. The lithium nickel-based transition metal composite oxide refers to the lithium nickel-based active material and the aluminum-containing coating as a whole.

[0038] In this article, "aluminum content in the aluminum-containing coating" can be measured by performing EDS on the positive electrode active material. EDS facilitates (e.g., allows) the measurement of the content of a specific element in the total elements contained on the surface of the positive electrode active material, where "%" can be on a molar basis. That is, the elemental composition of the aluminum-containing coating including a certain concentration of aluminum can be measured using EDS.

[0039] According to one embodiment, the aluminum-containing coating layer includes or consists of nickel, manganese and aluminum, and the aluminum content may refer to a ratio of the aluminum content to the total content of nickel, manganese and aluminum in the aluminum-containing coating layer.

[0040] If (when) the aluminum content of the aluminum-containing coating is less than 10 mol%, if (when) the positive electrode active material is placed at high temperature, the amount of degassing may increase and / or the high temperature life may deteriorate. If (when) the aluminum content of the aluminum-containing coating is greater than 35 mol%, the surface resistance may increase excessively, resulting in poor initial capacity characteristics, deterioration of capacity characteristics after repeated formation, and poor high temperature life. In an embodiment, the aluminum-containing coating may have an aluminum content of 15 mol% to 35 mol% or 20 mol% to 35 mol% as measured by EDS, based on the total amount of all elements in the aluminum-containing coating. For example, the aluminum-containing coating may have an aluminum content of 10 mol%, 11 mol%, 12 mol%, 13 mol%, 14 mol%, 15 mol%, 16 mol%, 17 mol%, 18 mol%, 19 mol%, 20 mol%, 21 mol%, 22 mol%, 23 mol%, 24 mol%, 25 mol%, 26 mol%, 27 mol%, 28 mol%, 20 mol%, 30 mol%, 31 mol%, 32 mol%, 33 mol%, 34 mol% or 35 mol%, based on the total amount of all elements in the aluminum-containing coating.

[0041] According to one embodiment, the aluminum-containing coating may have a nickel content (e.g., amount) of 30 mol% to 70 mol% measured by EDS based on the total amount of elements of the aluminum-containing coating. Within this range, the positive electrode active material can easily achieve improved capacity characteristics. For example, based on the total amount of all elements in the aluminum-containing coating, the aluminum-containing coating may have a nickel content of 35 mol% to 65 mol%, 35 mol% to 60 mol%, 40 mol% to 60 mol%, or 40 mol% to 60 mol% measured by EDS. For example, the aluminum-containing coating may have a nickel content of 30 mol%, 31 mol%, 32 mol%, 33 mol%, 34 mol%, 35 mol%, 36 mol%, 37 mol%, 38 mol%, 39 mol%, 40 mol%, 41 mol%, 42 mol%, 43 mol%, 44 mol%, 45 mol%, 46 mol%, 47 mol%, 48 mol%, 49 mol%, 50 mol%, 51 mol%, 52 mol%, 53 mol%, 54 mol%, 55 mol%, 56 mol%, 57 mol%, 58 mol%, 59 mol%, 60 mol%, 61 mol%, 62 mol%, 63 mol%, 64 mol%, 65 mol%, 66 mol%, 67 mol%, 68 mol%, 69 mol%, or 70 mol%, based on the total amount of all elements in the aluminum-containing coating.

[0042] According to one embodiment, the aluminum-containing coating may have a manganese content (e.g., amount) of 10 mol% to 50 mol% based on the total amount of elements of the aluminum-containing coating. Within this range, the positive electrode active material can easily achieve improved capacity characteristics. For example, based on the total amount of all elements in the aluminum-containing coating, the aluminum-containing coating may have a manganese content of 10 mol% to 40 mol%, 10 mol% to 30 mol%, or 10 mol% to 30 mol% as measured by EDS. For example, the aluminum-containing coating may have a manganese content of 10 mol%, 11 mol%, 12 mol%, 13 mol%, 14 mol%, 15 mol%, 16 mol%, 17 mol%, 18 mol%, 19 mol%, 20 mol%, 21 mol%, 22 mol%, 23 mol%, 24 mol%, 25 mol%, 26 mol%, 27 mol%, 28 mol%, 29 mol%, 30 mol%, 31 mol%, 32 mol%, 33 mol%, 34 mol%, 35 mol%, 36 mol%, 37 mol%, 38 mol%, 39 mol%, 40 mol%, 41 mol%, 42 mol%, 43 mol%, 44 mol%, 45 mol%, 46 mol%, 47 mol%, 48 mol%, 49 mol% or 50 mol% as measured by EDS, based on the total amount of all elements in the aluminum-containing coating.

[0043] According to one embodiment, in the aluminum-containing coating, the ratio of the aluminum content to the nickel content (Al:Ni) may be 0.2 to 0.8 (i.e., 0.2:1 to 0.8:1). Within this range, the positive electrode active material can easily achieve improved capacity characteristics and life. For example, the ratio of the aluminum content to the nickel content may be 0.3 to 0.8, 0.35 to 0.8, or 0.4 to 0.8. For example, the ratio of the aluminum content to the nickel content may be 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, or 0.8.

[0044] Here, the nickel content and the manganese content in the aluminum-containing coating can be measured by EDS.

[0045] According to one embodiment, the lithium nickel-based transition metal composite oxide may have a ratio (i.e., aluminum content ratio) of 5 to 20 (i.e., 5:1 to 20:1) calculated according to Equation 1. Within this range, the lithium nickel-based transition metal composite oxide (i.e., positive electrode active material) having a cobalt content of 0 mol% to 0.01 mol% may easily achieve an improvement in lifespan:

[0046] Equation 1

[0047] Ratio = B / A

[0048] Wherein A is the aluminum content of the lithium nickel transition metal composite oxide (for example, the total amount of aluminum in both the lithium nickel active material and the aluminum-containing coating), and

[0049] B is the aluminum content of the aluminum-containing coating layer of the lithium nickel-based transition metal composite oxide. That is, B is only the aluminum content in the aluminum-containing coating layer.

[0050] In Formula 1, A is the aluminum content (for example, in mol%) based on the total content of all metals except lithium in the lithium nickel-based transition metal composite oxide, and can be measured by, for example, an ICP method.

[0051] In Formula 1, B is the aluminum content based on the total content of all metals except lithium in the aluminum-containing coating layer of the lithium nickel-based transition metal composite oxide, and can be measured by, for example, an EDS method.

[0052] Equation 1 may be a standard for determining whether a lithium nickel-based transition metal composite oxide having a nickel content of 70 mol% or more and a cobalt content of 0 mol% to 0.01 mol% based on the total content of all metals other than lithium in the lithium nickel-based transition metal composite oxide has good life and capacity characteristics without degassing in a battery. For example, Equation 1 may be a standard for determining whether a lithium nickel-based transition metal composite oxide having a nickel content of 70 mol% or more, a cobalt content of 0 mol% to 0.01 mol% and an aluminum content of less than 4 mol%, each based on the total content of all metals other than lithium in the lithium nickel-based transition metal composite oxide, can have good life and capacity characteristics without degassing in a battery.

[0053] The lithium nickel-based transition metal composite oxide satisfying Equation 1 may be prepared by the method for preparing the lithium nickel-based transition metal composite oxide described below. The method for preparing the lithium nickel-based transition metal composite oxide will be described in more detail below.

[0054] For example, the ratio of Equation 1 may be 5 to 18, 6 to 17, or 7 to 17. For example, the ratio of Equation 1 may be 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5, 15, 15.5, 16, 16.5, 17, 17.5, 18, 18.5, 19, 19.5, or 20. Within these ranges, the positive electrode active material may have good characteristics in terms of capacity characteristics, lifespan, and suppression of degassing, and may be easily prepared. For example, the ratio of Equation 1 may be 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5, 15, 15.5, 16, 16.5, 17, 17.5, 18, 18.5, 19, 19.5, or 20.

[0055] According to one embodiment, the lithium nickel-based active material may include secondary particles prepared by aggregating a plurality of primary particles. The secondary particles may be aggregates of primary particles aggregated by a physical method and / or a chemical method.

[0056] The primary particles may have an average particle size of 0.05 μm to 0.5 μm, for example, an average particle size of 0.08 μm to 0.4 μm or 0.1 μm to 0.3 μm (100 nm to 300 nm). Within these ranges, the positive electrode active material can be easily prepared. For example, the primary particles may have an average particle size of 0.05 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm or 0.5 μm.

[0057] The secondary particles may have an average particle size of 10 μm to 20 μm, for example, 14 μm to 20 μm, 15 μm to 20 μm, or 16 μm to 20 μm. Within this range, the positive electrode active material can be easily prepared. For example, the secondary particles may have an average particle size of 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm, 15 μm, 15.5 μm, 16 μm, 16.5 μm, 17 μm, 17.5 μm, 18 μm, 18.5 μm, 19 μm, 19.5 μm, or 20 μm.

[0058] Herein, if (when) the active material particles have a spherical shape, "average particle size" refers to the average diameter of the active material particles. If the active material particles are not spherical, "average particle size" refers to the maximum value among the major axis lengths that can be obtained from the cross section of the particles. The average diameter can be measured using a particle size distribution (PSD) instrument or by SEM. The major axis length can be measured by SEM or the like.

[0059] The lithium nickel-based active material may include a lithium nickel-based active material having a cobalt content of 0 mol % to 0.01 mol %.

[0060] For example, the lithium nickel-based active material may be a compound represented by Formula 1:

[0061] Formula 1

[0062] Li a1 Ni x1 M 1 y1 M 2 1-x1-y1 O2,

[0063] where 0.9≤a1≤1.8, 0.3≤x1≤1, and 0≤y1≤0.7, and M 1 and M 2 Each is independently selected from Al, B, Ce, Cr, F, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr, Ca, Ba, Ti, Zr, Zn, Fe, rare earth elements and combinations thereof.

[0064] In some embodiments, in Formula 1, 0.3≤x1≤1 and 0≤y1≤0.7; 0.4≤x1≤1 and 0≤y1≤0.6; 0.5≤x1≤1 and 0≤y1≤0.5; 0.6≤x1≤1 and 0≤y1≤0.4; 0.7≤x1≤1 and 0≤y1≤0.3; 0.8≤x1≤1 and 0≤y1≤0.2; or 0.9≤x1≤1 and 0≤y1≤0.1.

[0065] Next, a method for preparing the positive electrode active material will be described.

[0066] The method for preparing a positive electrode active material comprises: preparing a primary positive electrode active material by wet-coating the surface of a lithium nickel-based active material with an aluminum source in a first solution containing a lithium nickel-based active material having a cobalt content of 0 mol% to 0.01 mol%, an aluminum source and a solvent; and preparing a final positive electrode active material by heat treatment of the primary positive electrode active material, wherein the aluminum source is present in the first solution in an amount of less than 2 mol% based on the total content of all metals other than lithium in the lithium nickel-based active material, and the heat treatment is carried out at a temperature greater than 700°C to 750°C.

[0067] This method can facilitate the preparation of a positive electrode active material with an aluminum content in an aluminum-containing coating, whereby the positive electrode active material can improve capacity and life characteristics while suppressing degassing.

[0068] (1) Prepare a lithium nickel-based active material with a cobalt content of 0 mol% to 0.01 mol%.

[0069] The lithium nickel-based active material can be prepared, for example, by mixing a nickel-based active material precursor and a lithium source in a predetermined molar ratio and subjecting the mixture to preliminary heat treatment.

[0070] The nickel-based active material precursor can be, for example, a compound represented by Formula 2:

[0071] Formula 2

[0072] Ni 1-y-z M 1 y M 2 z (OH)2,

[0073] where 0 < y < 0.5, 0.8 ≤ 1 - y - z < 1, and 0 ≤ z < 0.5, and

[0074] M 1 and M 2 are each independently Al, B, Ce, Cr, F, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr, Ca, Ba, Ti, Zr, Zn, Fe, a rare earth element, or a combination thereof.

[0075] The nickel-based active material precursor can be prepared by co-precipitating a nickel precursor and a precursor of another transition metal. For example, the nickel-based active material precursor can be a hydroxide or oxide containing nickel and other metals.

[0076] The nickel-based active material precursor can be prepared by mixing a nickel precursor, a manganese precursor, and an aluminum precursor in a first solvent. The nickel precursor, manganese precursor, and aluminum precursor can be any suitable substances available in the art, and the content of each of the nickel precursor, manganese precursor, and aluminum precursor is stoichiometrically controlled to obtain a compound of Formula 2.

[0077] The first solvent can be water, ethanol, propanol, butanol, etc. Additionally, relative to 100 parts by weight of all the nickel precursor, manganese precursor, and aluminum precursor, the first solvent is present in an amount of 100 parts by weight to 2,000 parts by weight.

[0078] According to one embodiment, the nickel-based active material precursor can be a secondary particle prepared by aggregation of a plurality of primary particles.

[0079] The lithium source may include, for example, lithium hydroxide, lithium fluoride, lithium carbonate, lithium sulfate, lithium nitrate, or a mixture thereof. The mixing ratio of the lithium source and the nickel-based active material precursor may be stoichiometrically controlled, for example, to prepare a lithium nickel-based active material represented by Formula 1.

[0080] The mixing of the lithium source and the nickel-based active material precursor may be dry mixed and may be performed using a mixer or the like. Dry mixing may be performed by grinding. Although the grinding conditions are not particularly limited, grinding may be performed to allow little or no deformation (such as refining the nickel-based active material precursor used as a starting material). A mixture (e.g., a mixture required for producing the nickel-based active material represented by Chemical Formula 1) may be obtained by grinding the lithium source and the nickel-based active material precursor at 300 rpm to 3,000 rpm. If the internal temperature of the mixer rises to above 30°C during the grinding process, a cooling process may be performed to keep the interior of the mixer at room temperature (25°C).

[0081] The mixture is treated with a preliminary heat treatment in air or under an oxygen atmosphere. The preliminary heat treatment can be performed, for example, at 600° C. to 900° C., for example, at 650° C. to 900° C., thereby producing a lithium nickel-based active material (e.g., a lithium nickel-based transition metal composite oxide).

[0082] When the nickel-based active material precursor is mixed with the lithium source, a second solvent may be further used. Similar to the first solvent described above, the second solvent may include water, ethanol, butanol, propanol, etc., and the second solvent may be present in an amount of 100 to 2,000 parts by weight relative to 100 parts by weight of the lithium source.

[0083] A complexing agent and a pH adjusting agent may be added to a mixture containing a nickel-based active material precursor and a lithium source and mixed therewith. The complexing agent may include, for example, aqueous ammonia as an ammonium ion source, and the pH adjusting agent may include, for example, a sodium hydroxide solution, etc. By adjusting the content of the pH adjusting agent, the pH of the resulting product is adjusted within the range of 11 to 13.

[0084] (2) preparing a primary positive electrode active material by wet coating a surface of a lithium nickel-based active material with an aluminum source in a first solution containing a lithium nickel-based active material, an aluminum source, and a solvent, wherein the aluminum source is present in the first solution in an amount of less than 2 mol% based on the total content of all metals other than lithium in the lithium nickel-based active material.

[0085] Based on the total content of all metals other than lithium in the lithium nickel active material, the aluminum source is present in an amount of less than 2 mol%. If the content of the aluminum source exceeds 2 mol%, it is difficult for the aluminum-containing coating to have the aforementioned aluminum content, resulting in poor capacity characteristics. For example, based on the total content of all metals other than lithium in the lithium nickel active material, the aluminum source may be present in an amount of 0.1 mol% to less than 2 mol% or 0.5 mol% to 1 mol%.

[0086] According to one embodiment, the aluminum source may include a suitable (e.g., known to those skilled in the art) material for coating aluminum by wet coating. Wet coating allows the surface of the lithium nickel-based active material to be uniformly coated with the aluminum source. For example, the aluminum source may include at least one of aluminum sulfate, aluminum nitrate, aluminum carbonate, and aluminum hydroxide.

[0087] According to one embodiment, the solvent may be any suitable solvent (eg, known to those skilled in the art) for coating aluminum by wet coating. For example, the solvent may include at least one of distilled water, ethanol, isopropanol, and n-propanol.

[0088] Wet coating can be performed by stirring the first solution at a temperature of 5° C. to 30° C. for 5 minutes to 2 hours.

[0089] (3) The final positive electrode active material is prepared by heat treatment of the preliminary positive electrode active material, wherein the heat treatment is performed at a temperature greater than 700° C. to 750° C.

[0090] The heat treatment is performed at a temperature greater than 700°C to 750°C. Heat treatment temperatures at 700°C or lower may cause degradation of initial capacity, degradation of formation capacity after repeated cycles, and degradation of life at high temperatures. Heat treatment at a temperature greater than 750°C may result in large amounts of outgassing and poor life at high temperatures.

[0091] According to one embodiment, the heat treatment temperature (ie, secondary calcination temperature) may be lower than the primary heat treatment temperature (ie, primary calcination temperature) by 95° C. or more (eg, 95° C. to 150° C.) Within these ranges, a positive electrode active material may be easily prepared.

[0092] Rechargeable lithium battery

[0093] According to another embodiment, a rechargeable lithium battery includes: a positive electrode including a positive electrode active material for a rechargeable lithium battery; a negative electrode; and an electrolyte.

[0094] The positive electrode for a rechargeable lithium battery may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector. The positive electrode active material layer may include the above-mentioned positive electrode active material, and may further include a binder and / or a conductive material.

[0095] In one embodiment, the positive electrode may further include a component capable of functioning as a sacrificial positive electrode.

[0096] The positive electrode active material may be present in an amount of 90 to 99 wt % based on 100 wt % of the positive electrode active material layer, and each of the binder and the conductive material may be present in an amount of 0.5 to 5 wt % based on 100 wt % of the positive electrode active material layer.

[0097] The positive electrode active material includes the positive electrode active material according to one or more embodiments of the present disclosure. The description of the positive electrode active material according to the embodiment is the same as that described above.

[0098] In addition to the positive electrode active material according to the embodiment of the present disclosure, the positive electrode active material may further include different positive electrode active materials for rechargeable lithium batteries. For example, the positive electrode active material for rechargeable lithium batteries may include at least one composite oxide of lithium and a metal selected from cobalt, manganese, nickel, and a combination thereof.

[0099] The composite oxide may be a lithium transition metal composite oxide. For example, the composite oxide may include lithium nickel oxide, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate compound or a combination thereof.

[0100] By way of example, the composite oxide may be a compound represented by any one of the following chemical formulas: Li a A 1- b X b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); Li a Mn 2-b X b O 4-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, 0<α<2); Li a Ni 1-b-c Mn b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, 0<α<2); Li a Nib Co c L 1 d G e O2 (0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0≤e≤0.1); Li a NeG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a CoG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-b G b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn b O4(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-g G g PO4(0.90≤a≤1.8, 0≤g≤0.5); Li (3-f) Fe2(PO4)3(0≤f≤2); and Li a FePO4(0.90≤a≤1.8).

[0101] In the above formula, A is Ni, Co, Mn or a combination thereof; X is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or a combination thereof; D is O, F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; and L 1 It is Mn, Al or a combination thereof.

[0102] In one embodiment, the positive electrode active material may be a positive electrode active material with a high nickel content, based on 100 mol% of metals other than lithium in the lithium transition metal composite oxide (i.e., the positive electrode active material with a high nickel content), the positive electrode active material with a high nickel content includes 80 mol% or more, 85 mol% or more, 90 mol% or more, 91 mol% or more, or 94 mol% to 99 mol% of nickel. The positive electrode active material with a high nickel content can achieve high capacity and can therefore be applied to high capacity / high energy density rechargeable lithium batteries.

[0103] The binder is used to attach the positive electrode active material particles to each other and also to attach the positive electrode active material to the positive electrode current collector. The binder may include, for example, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth) acrylated styrene-butadiene rubber, epoxy resin, (meth) acrylic resin, polyester resin, nylon, etc., but is not limited thereto.

[0104] The conductive material is used to impart conductivity to the electrode, and may be any suitable conductive material that does not cause chemical changes in the constructed battery cell. The conductive material may include, for example, carbon materials (such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.); metal-based materials in the form of metal powder or metal fiber containing copper, nickel, aluminum, silver, etc.; conductive polymers (such as polyphenylene derivatives, etc.); and mixtures thereof.

[0105] The positive electrode current collector may be an Al foil, but is not limited thereto.

[0106] The negative electrode for a rechargeable lithium battery includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material and may further include a binder and / or a conductive material.

[0107] For example, the negative electrode active material layer may include 90 wt % to 99 wt % of the negative electrode active material, 0.5 wt % to 5 wt % of the binder, and 0 wt % to 5 wt % of the conductive material, based on 100 wt % of the negative electrode active material layer.

[0108] The negative electrode active material includes a material that allows reversible intercalation / deintercalation of lithium ions, lithium metal, a lithium metal alloy, a material that allows lithium to be doped thereinto and dedoped therefrom, or a transition metal oxide.

[0109] The material that allows reversible intercalation / deintercalation of lithium ions may include a carbon-based negative electrode active material, for example, crystalline carbon, amorphous carbon, or a combination thereof. Crystalline carbon may include, for example, graphite (such as natural graphite or artificial graphite) in the form of amorphous, plate-like, flaky, spherical, or fibrous shapes, and amorphous carbon may include, for example, soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.

[0110] As the lithium metal alloy, alloys of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn can be used.

[0111] The material that allows lithium doping into it and de-doping from it can be a Si-based negative electrode material or a Sn-based negative electrode material. The Si-based negative electrode material can be silicon, a silicon-carbon composite, SiO x (0 < x ≤ 2), a Si-Q alloy (where Q is selected from alkali metals, alkaline earth metals, Group XIII elements, Group XIV elements (except Si), Group XV elements, Group XVI elements, transition metals, rare earth elements, and combinations thereof), or a combination thereof. The Sn-based negative electrode material can be Sn, SnO x (0 < x ≤ 2) (for example, SnO2), a Sn alloy, or a combination thereof.

[0112] The silicon-carbon composite can be a composite of silicon and amorphous carbon. According to one embodiment, the silicon-carbon composite can be prepared in the form of silicon particles with an amorphous carbon coating formed on its surface. For example, the silicon-carbon composite can include secondary particles (cores) composed of primary silicon particles and an amorphous carbon coating (shells) formed on the surfaces of the secondary particles. Amorphous carbon can also be placed between the primary silicon particles such that, for example, the primary silicon particles are coated with amorphous carbon. The secondary particles can be dispersed in an amorphous carbon matrix.

[0113] The silicon-carbon composite can further include crystalline carbon. For example, the silicon-carbon composite can include: a core containing crystalline carbon and silicon particles, and an amorphous carbon coating formed on the core.

[0114] The Si-based negative electrode material or the Sn-based negative electrode material can be used in combination with a carbon-based negative electrode material.

[0115] The binder is used to attach the negative electrode active material particles to each other and is also used to attach the negative electrode material to the negative electrode current collector. The binder can be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.

[0116] The non-aqueous binder can include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0117] The aqueous binder can be selected from the group consisting of: styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, poly(ethylene oxide), polyvinylpyrrolidone, poly(epichlorohydrin), polyphosphazene, poly(meth)acrylonitrile, ethylene-propylene-diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.

[0118] If (when) an aqueous binder is used as a binder in the negative electrode active material layer, a cellulose compound capable of imparting viscosity may be further included. The cellulose compound may be carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose or a mixture of alkali metal salts thereof. The alkali metal may be Na, K or Li.

[0119] The dry binder may be a polymeric material capable of fiberization, and may include, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.

[0120] The conductive material is used to impart conductivity to the electrode, and may be any suitable conductive material that does not cause chemical changes in the constructed battery cell. For example, the conductive material may include: for example, carbon materials (such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.); metal-based materials in the form of metal powder or metal fiber containing copper, nickel, aluminum, silver, etc.; conductive polymers (such as polyphenylene derivatives, etc.); or mixtures thereof.

[0121] The negative electrode current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0122] The electrolyte for a rechargeable lithium battery includes a non-aqueous organic solvent and a lithium salt.

[0123] The nonaqueous organic solvent serves as a medium through which ions participating in the electrochemical reaction of the battery cell can move.

[0124] The non-aqueous organic solvent may include a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, an alcohol solvent, an aprotic solvent, or a combination thereof.

[0125] The carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc.

[0126] The ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonolactone, valerolactone, caprolactone, and the like.

[0127] Ether solvents may include dibutyl ether, tetraglyme, diglyme, ethylene glycol dimethyl ether, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. In addition, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitrile, such as R-CN (wherein R is a linear, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, and may include a double bond, an aromatic ring or an ether group); amides (such as dimethylformamide); dioxolanes (such as 1,3-dioxolanes, 1,4-dioxolanes, etc.); sulfolane; and the like.

[0128] The nonaqueous organic solvent may be used alone or as a mixture thereof.

[0129] When a carbonate-based solvent is used, a mixture of a cyclic carbonate and a chain carbonate may be used, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of 1:1 to 1:9.

[0130] Lithium salts are substances that are soluble in non-aqueous organic solvents and used as a lithium ion source in batteries, ensuring the basic operation of rechargeable lithium batteries while facilitating the transfer of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts may include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N(Lithium bis(fluorosulfonyl)imide (LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are each an integer of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFBOP) and lithium bis(oxalato)borate (LiBOB).

[0131] According to the type or kind of the rechargeable lithium battery, the separator may be inserted between the positive electrode and the negative electrode. For such a separator, a polyethylene separator, a polypropylene separator, a polyvinylidene fluoride separator or at least two layers thereof (such as a polyethylene / polypropylene double-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polyethylene / polyethylene / polypropylene three-layer separator, etc.) may be used.

[0132] The separator may include a porous substrate and a coating on one or both surfaces of the porous substrate, the coating including an organic material, an inorganic material, or a combination thereof.

[0133] The porous substrate may be a polymer layer formed from: a polymer selected from polyolefins (such as polyethylene, polypropylene, etc.), polyesters (such as polyethylene terephthalate, polybutylene terephthalate, etc.), polyacetals, polyamides, polyimides, polycarbonates, polyether ketones, polyaryletherketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene oxides, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fibers, and polytetrafluoroethylene (e.g., Teflon), copolymers thereof, or mixtures thereof.

[0134] The organic material may include a polyvinylidene fluoride polymer or a (meth)acrylic polymer.

[0135] The inorganic material may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite and combinations thereof, but is not limited thereto.

[0136] The organic material and the inorganic material may exist in a mixed state in one coating layer, or may exist in the form of a stacked structure of a coating layer including an organic material and a coating layer including an inorganic material.

[0137] Rechargeable lithium batteries may be classified into cylindrical secondary batteries, faceted (eg, prismatic) secondary batteries, pouch-type or quasi-secondary batteries, coin-type secondary batteries, etc., based on their shapes.

[0138] Figure 1 to Figure 4 is a schematic diagram of a rechargeable lithium battery according to an embodiment of the present disclosure, wherein Figure 1 A cylindrical battery is shown, Figure 2 A prismatic cell is shown, and Figure 3 and Figure 4 Pouch type or similar battery is shown. Figure 1 to Figure 4 , the rechargeable lithium battery 100 may include: an electrode assembly 40 in which a separator 30 is inserted between a positive electrode 10 and a negative electrode 20; and a case 50 in which the electrode assembly 40 is accommodated. The positive electrode 10, the negative electrode 20, and the separator 30 may be built in an electrolyte. Figure 1 As shown, the rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50. Figure 2 As shown, the rechargeable lithium battery 100 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. Figure 3 and Figure 4 , the rechargeable lithium battery 100 may include electrode tabs 70 , ie, a positive electrode tab 71 and a negative electrode tab 72 , which serve as an electrical path for introducing current formed in the electrode assembly 40 to the outside.

[0139] The rechargeable lithium battery according to an embodiment of the present disclosure may be applied to automobiles, mobile phones, and / or various other electronic devices, but is not limited thereto.

[0140] The following examples and comparative examples are provided to highlight the features of one or more embodiments, but it will be understood that the examples and comparative examples should not be interpreted as limiting the scope of the embodiments, and the comparative examples should not be interpreted as being outside the embodiments. Further, it will be understood that the embodiments are not limited to the specific details described in the examples and comparative examples.

[0141] Example 1: Preparation of positive electrode active material

[0142] Al2(SO4)3·(H2O) 18 was used as an aluminum precursor, NiSO4.(H2O)6 was used as a nickel precursor, and MnSO4.(H2O)6 was used as a manganese precursor.

[0143] The aluminum precursor Al2(SO4)3·(H2O) 18 Mix with NaOH, NH4OH and water to prepare an aqueous solution of aluminum precursor.

[0144] A nickel precursor NiSO4.(H2O)6 and a manganese precursor MnSO4.(H2O)6 are mixed with water to prepare an aqueous solution of a nickel precursor and an aqueous solution of a manganese precursor, respectively.

[0145] The aqueous solution of aluminum precursor is placed in a reactor, the aqueous solution of nickel precursor and the aqueous solution of manganese precursor are added dropwise to the reactor to obtain a reaction mixture, and then the reaction mixture is stirred for 10 to 20 hours. The content of each of the nickel precursor, manganese precursor and aluminum precursor in the reaction mixture is stoichiometrically controlled until the molar ratio of nickel, manganese and aluminum reaches 75:23:2.

[0146] An aqueous solution of sodium hydroxide was added to the reaction mixture to adjust the pH of the reaction mixture to 10 to 12. The resulting product obtained by filtering and washing the resulting precipitate was dried in a vacuum at 100° C. to prepare nickel manganese aluminum hydroxide (Ni 0.75 Mn 0.23 Al 0.02 OH)2) powder, which is a nickel-manganese precursor doped with aluminum (as a nickel-based active material precursor).

[0147] After mixing nickel manganese aluminum hydroxide with lithium hydroxide (LiOH) as a lithium source, the mixture is placed in a furnace, and then, while supplying O2 to the furnace, a preliminary calcination (i.e., preliminary heat treatment) is performed at 845°C for 15 hours, followed by drying. The content of each of the nickel manganese aluminum hydroxide and the lithium source is controlled so that the mixing ratio of all metals except lithium in the nickel manganese aluminum hydroxide to lithium reaches 1:1.03 in mole, thereby preparing a lithium nickel-based active material.

[0148] As an aluminum source, aluminum sulfate was added to the lithium nickel-based active material (so that the aluminum content was 1 mol% based on the total content of all metals except lithium in the lithium nickel-based active material) and wet-coated in distilled water to prepare a primary positive electrode active material.

[0149] The primary positive electrode active material was subjected to secondary calcination (i.e., heat treatment) at 750°C for 20 hours to prepare the final nickel-based active material (LiNi 0.745 Mn 0.225 Al 0.03 O2).

[0150] Example 2: Preparation of positive electrode active material

[0151] The final nickel-based active material (LiNi 0.745 Mn 0.225 Al 0.03 O2), except that a secondary calcination was carried out at 725°C for 20 hours.

[0152] Example 3: Preparation of positive electrode active material

[0153] The final nickel active material (LiNi 0.745 Mn 0.235 Al 0.02 O2), but stoichiometrically controlling the content of each of the nickel precursor, the manganese precursor and the aluminum precursor until the molar ratio of nickel, manganese and aluminum reaches 75:24:1.

[0154] Comparative Example 1: Preparation of positive electrode active material

[0155] The final nickel-based active material (LiNi 0.745 Mn 0.225 Al 0.03 O2), except that a secondary calcination was carried out at 825°C for 20 hours.

[0156] Comparative Example 2: Preparation of positive electrode active material

[0157] The final nickel-based active material (LiNi0.745 Mn 0.225 Al 0.03 O2), but a secondary calcination was carried out at 700°C for 20 hours.

[0158] Comparative Example 3: Preparation of positive electrode active material

[0159] The final nickel active material (LiNi 0.74 Mn 0.22 Al 0.04 O2), except that the content of each of the nickel precursor, the manganese precursor and the aluminum precursor is stoichiometrically controlled until the molar ratio of nickel, manganese and aluminum reaches 75:23:2, and 2 mol% of aluminum is added instead of 1 mol% of aluminum.

[0160] Table 1 summarizes the preparation processes of the positive electrode active materials in Examples and Comparative Examples.

[0161] After measuring the ICP values ​​of the positive electrode active materials prepared in the examples and comparative examples, the content ratio (e.g., in mol%) of Ni:Mn:Al in all elements except lithium in the positive electrode active materials (i.e., Ni:Mn:Al ratio) was obtained based on the ICP measurement. The results are shown in Table 1.

[0162] Table 1

[0163]

[0164] For the positive electrode active materials prepared in the examples and comparative examples, the content ratios of nickel, manganese and aluminum on the uppermost surface of the positive electrode active materials were measured by energy dispersive X-ray spectroscopy (EDS) at 1000 times magnification. The measurements were performed at five different points on the uppermost surface of the positive electrode active material, and the average value of each of nickel, manganese and aluminum was calculated.

[0165] Then, the aluminum content ratio was calculated according to Equation 1 based on the following: A, which is the aluminum content based on the sum (i.e., total content) of nickel, aluminum, and manganese in the positive electrode active material in Table 1, and B, which is the aluminum content based on the sum (i.e., total content) of nickel, manganese, and aluminum on the uppermost surface of the positive electrode active material. The results are shown in Tables 2 and Figure 5 shown.

[0166] Table 2

[0167]

[0168] Refer to Table 2 and Figure 5It can be seen that the positive electrode active material of the embodiment has an aluminum content of 10 mol% to 35 mol% in the aluminum-containing coating layer measured by EDS. On the contrary, it can be seen that the aluminum content of the positive electrode active materials of Comparative Examples 1 to 3 is outside the range of 10 mol% to 35 mol%.

[0169] Preparation of rechargeable lithium batteries

[0170] The positive electrode active material slurry was prepared by mixing the positive electrode active material prepared in each of the examples and the comparative examples, the carbon conductor (carbon nanotubes) and the polyvinylidene fluoride (PVDF) binder solution. In the positive electrode active material slurry, the weight ratio of the positive electrode active material, the carbon conductor and the binder was 97.7:1.0:1.3. The prepared positive electrode active material slurry was coated with a thick film coater at 27 mg / cm 2 The loading level of 200 Å was coated on an aluminum current collector having a thickness of 13.5 μm, dried at 120° C. for 1 hour or more, and roll-pressed to prepare a positive electrode.

[0171] Graphite powder as a negative electrode active material was mixed with a mixture of styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) in a weight ratio of 1:1 at a weight ratio of 97:3 to prepare a negative electrode active material slurry.

[0172] The prepared negative electrode active material slurry was 2 The coating was coated on a copper foil current collector having a thickness of 8 μm at a loading level. The coated copper foil current collector was dried at 100° C. for 1 hour or more and then roll-pressed to prepare a composite density of 1.5 g / cm 3 of the negative electrode.

[0173] A rechargeable lithium battery with a capacity of 30 mAh was prepared using the positive and negative electrodes together with a polyethylene separator (Separator, STAR 20, Asahi) and an electrolyte in which 1.15 M LiPF6 was dissolved in a mixed solvent of EC (ethylene carbonate), MEC (ethyl methyl carbonate) and DMC (dimethyl carbonate) (2:4:4 volume ratio).

[0174] The following characteristics of the prepared rechargeable lithium battery were evaluated, and the results are shown below.

[0175] (1) Initial (1 cycle) formation capacity and efficiency: At 25°C, the initial charge capacity was measured by charging each of the rechargeable lithium batteries from 2.8 V to an upper voltage limit of 4.4 V at a constant current of 0.2 C, charging the battery under constant voltage conditions until the current dropped to a termination condition of 0.05 C, and then discharging at 0.2 C to a discharge termination voltage of 2.8 V to measure the initial discharge capacity (i.e., initialization formation capacity). The ratio of the initial discharge capacity to the initial charge capacity (as efficiency) was calculated. The results are shown in Figure 6 and are shown in Table 3.

[0176] (2) Formation capacity after repeated cycles (5 cycles): The formation capacity was measured after 5 cycles of charge / discharge under the conditions described in (1). Figure 6 and as shown in Table 3. (Forming stage)

[0177] (3) High temperature life at 45°C: At 45°C, a rechargeable lithium battery that has passed the formation stage is charged from 2.8 V to an upper limit voltage of 4.4 V at a constant current of 0.5 C, and is charged under constant voltage conditions while maintaining 4.4 V until the current drops to a termination condition of 0.05 C; then, the battery is discharged at a constant current of 0.5 C until the voltage drops to 2.8 V during discharge to measure the discharge capacity; the cycle is repeated 150 times.

[0178] The high temperature life is calculated by dividing the discharge capacity per cycle by the weight of the positive electrode active material. Figure 7 and are shown in Table 3.

[0179] (4) Degassing amount at 90°C for 4 hours: After evaluating the formation capacity in (1), the rechargeable lithium battery was fully charged to 4.4V and completely immersed in water at 90°C to obtain an initial volume V1. The rechargeable lithium battery was then placed in water at 90°C for 4 hours to obtain a volume V2. V1 was subtracted from V2 (i.e., V2-V1) to calculate the volume increase. The degassing amount per gram weight of the positive electrode active material was calculated based on the buoyancy and volume increase. The results are in Figure 8 and are shown in Table 3.

[0180] Table 3

[0181]

[0182] *In Table 3, “-” indicates “not evaluated”.

[0183] Reference Table 3, Figure 6 , Figure 7 and Figure 8 It can be seen that the positive electrode active material of the embodiment suppresses the side reaction of forming gas and has good high temperature life and high capacity.

[0184] On the other hand, referring to Table 3, Figure 6 , Figure 7 and Figure 8 It can be seen that both Comparative Example 1 having an aluminum-containing coating with an aluminum content of less than 10 mol % and Comparative Example 2 having an aluminum content of more than 35 mol % measured by EDS fail to provide all the enhanced effects of the above-mentioned embodiments.

[0185] According to one or more embodiments, the positive electrode active material includes a lithium nickel active material and an aluminum-containing coating on the surface of the lithium nickel active material. The aluminum-containing coating and the lithium nickel active material together form a lithium nickel transition metal composite oxide. In some embodiments, the lithium nickel active material is represented by Formula 1. In some embodiments, the positive electrode active material does not include cobalt or includes cobalt in an amount not exceeding 0.01 mol%, includes nickel in an amount of 70 mol% or more, includes manganese in an amount of 10 mol% or more, and includes aluminum in an amount of less than 4 mol% (including both aluminum in the lithium nickel active material and aluminum in the aluminum-containing coating). And, in the aluminum-containing coating, the aluminum content measured by EDS is 10 mol% to 35 mol% based on the total amount of elements in the coating. The aluminum-containing coating may further include nickel in an amount of 30 mol% to 70 mol% measured by EDS, and include manganese in an amount of 10 mol% to 50 mol% measured by EDS, each amount based on the total amount of elements in the coating.

[0186] As used herein, the terms "use," "using," and "used" may be considered synonymous with the terms "utilize," "utilizing," and "utilized," respectively. As used herein, expressions such as "at least one of," "one of," and "selected from," when preceding / following a list of elements, modify the entire list of elements and do not modify the individual elements of the list. For example, "at least one selected from a, b, and c," "at least one of a, b, and c" may indicate only a, only b, only c, both a and b (e.g., simultaneously), both a and c (e.g., simultaneously), both b and c (e.g., simultaneously), all of a, b, and c, or variations thereof.

[0187] When describing embodiments of the present inventive concepts, the use of “may” refers to “one or more embodiments of the present inventive concepts”.

[0188] As used herein, the term "about" and similar terms are used as terms of approximation rather than as terms of degree, and are intended to account for the inherent deviations of measured or calculated values ​​that will be recognized by one of ordinary skill in the art. "About" as used herein includes the stated value and means within an acceptable range of deviations of the particular value determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" may mean within one or more standard deviations, or within ±30%, ±20%, ±10%, or ±5% of the stated value.

[0189] Any numerical range set forth in this article is intended to include all sub-ranges of the same numerical precision falling within the set forth range. For example, the range of "1.0-10.0" is intended to be included between the set forth minimum value 1.0 and the set forth maximum value 10.0 (and including the end value), that is, all sub-ranges (such as, for example, 2.4-7.6) having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0. Any maximum numerical limit set forth in this article is intended to include all lower numerical limits falling therein, and any minimum numerical limit set forth in this specification is intended to include all higher numerical limits falling therein. Accordingly, the applicant reserves the right to modify this specification (including claims) to explicitly set forth any sub-range falling within the range explicitly set forth in this article.

[0190] Here, unless otherwise specified, steps, tasks, or actions listed in a particular order do not necessarily mean that the invention or claims require that particular order. That is, as a general rule, unless the steps, tasks, or actions of a method (e.g., the method statement) actually set forth an order, the steps, tasks, or actions should not be construed as requiring an order.

[0191] The battery management system (BMS) device and / or any other related device or component according to the embodiments of the present invention described herein may be implemented using any appropriate hardware, firmware (e.g., a dedicated integrated circuit), software, or a combination of software, firmware, and hardware. For example, the various components of the device may be formed on an integrated circuit (IC) chip or on a separate IC chip. Further, the various components of the device may be implemented on a flexible printed circuit film, a tape carrier package (TCP), or a printed circuit board (PCB), or formed on a substrate. Further, the various components of the device may be processes or threads running on one or more processors in one or more computing devices, executing computer program instructions and interacting with other system components to perform the various functions described herein. The computer program instructions are stored in a memory, which may be implemented in a computing device using a standard memory device (such as, for example, a random access memory (RAM)). The computer program instructions may also be stored in other non-temporary computer-readable media (such as, for example, a CD-ROM, a flash drive, etc.). Moreover, those skilled in the art should recognize that, without departing from the scope of the present disclosure, the functions of various computing devices may be combined or integrated into a single computing device, or the functions of a particular computing device may be distributed on one or more other computing devices.

[0192] Although the present disclosure has been described with reference to some embodiments and drawings, it should be understood that the present disclosure is not limited thereto and that various modifications, changes, variations, and equivalent embodiments may be made by those skilled in the art without departing from the spirit and scope of the present disclosure.

Claims

1. A positive electrode active material for a rechargeable lithium battery, the positive electrode active material comprising a lithium nickel transition metal composite oxide, The lithium nickel transition metal composite oxide comprises a lithium nickel active material and an aluminum-containing coating formed on the surface of the lithium nickel active material. wherein in the lithium nickel transition metal composite oxide, the amount of nickel is 70 mol% or more, and the amount of cobalt is 0 mol% to 0.01 mol%, the amount of nickel and the amount of cobalt being each based on the total molar amount of all metals other than lithium in the lithium nickel transition metal composite oxide, and The amount of aluminum in the aluminum-containing coating layer is 10 mol % to 35 mol % based on the total amount of all elements in the aluminum-containing coating layer measured by EDS.

2. The positive electrode active material according to claim 1, wherein in the positive electrode active material, a total amount of aluminum is less than 4 mol% based on the total molar amount of all metals except lithium in the lithium nickel-based transition metal composite oxide. 3 . The positive electrode active material of claim 1 , wherein in the aluminum-containing coating layer, a ratio of the amount of aluminum to the amount of nickel measured by EDS is 0.2:1 to 0.8:

1.

4. The positive electrode active material according to claim 1, wherein the lithium nickel transition metal composite oxide has an aluminum content ratio of 5 to 20 calculated according to equation 1: Equation 1 Aluminum content ratio = B / A wherein A is the amount of aluminum in the lithium nickel transition metal composite oxide, and B is the amount of aluminum in the aluminum-containing coating layer in the lithium nickel-based transition metal composite oxide.

5. The positive electrode active material of claim 1 , wherein in the aluminum-containing coating layer, the amount of nickel is 30 mol % to 70 mol %, and the amount of manganese is 10 mol % to 50 mol %, the amount of nickel and the amount of manganese being each based on the total amount of all elements in the aluminum-containing coating layer measured by EDS.

6. The positive electrode active material according to claim 1, wherein the lithium nickel-based active material is represented by Formula 1: Formula 1 Li a1 Ni x1 M 1 y1 M 2 1-x1-y1 O2, where 0.9≤a1≤1.8, 0.3≤x1≤1, and 0≤y1≤0.7, and M 1 and M 2 Each is independently selected from Al, B, Ce, Cr, F, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr, Ca, Ba, Ti, Zr, Zn, Fe, rare earth elements and combinations thereof. 7 . The positive electrode active material of claim 1 , wherein the lithium nickel-based active material comprises secondary particles comprising aggregates of a plurality of primary particles. 8 . The positive electrode active material according to claim 1 , wherein the lithium nickel-based transition metal composite oxide comprises a lithium nickel manganese aluminum-based transition metal composite oxide.

9. The positive electrode active material according to claim 8, wherein in the lithium nickel manganese aluminum-based transition metal composite oxide, the amount of nickel is 70 mol% or more based on the total molar amount of nickel, manganese and aluminum.

10. The positive electrode active material according to claim 8, wherein in the lithium nickel manganese aluminum-based transition metal composite oxide, the amount of manganese is 10 mol% or more based on the total molar amount of nickel, manganese and aluminum.

11. The positive electrode active material according to claim 8, wherein in the lithium nickel manganese aluminum-based transition metal composite oxide, the amount of aluminum is less than 4 mol% based on the total molar amount of nickel, manganese and aluminum.

12. The positive electrode active material according to claim 1, wherein the lithium nickel-based active material comprises secondary particles comprising aggregates of a plurality of primary particles, The primary particles have an average particle size of 0.05 μm to 0.5 μm, and the secondary particles have an average particle size of 10 μm to 20 μm. 13 . The positive electrode active material of claim 1 , wherein the lithium nickel-based active material has a cobalt content of 0 mol % to 0.01 mol % based on the total molar amount of all metals except lithium in the lithium nickel-based active material.

14. A method for preparing a positive electrode active material for a rechargeable lithium battery, the method comprising: Prepare a primary positive electrode active material by wet coating the surface of a lithium nickel-based active material having a cobalt content of 0 mol% to 0.01 mol% with an aluminum source in a first solution, wherein the first solution comprises the lithium nickel-based active material, the aluminum source and a solvent; and The positive electrode active material is prepared by heat treating the primary positive electrode active material at a temperature greater than 700° C. to 750° C., Wherein, based on the total molar amount of all metals except lithium in the lithium nickel-based active material, the aluminum of the aluminum source is present in the first solution in an amount of less than 2 mol %.

15. A rechargeable lithium battery comprising: A positive electrode comprising the positive electrode active material according to any one of claims 1 to 13 or the positive electrode active material prepared by the method according to claim 14; a negative electrode; and an electrolyte.

Citation Information

Patent Citations

  • Battery cell tracking device

    KR1020230148103A